Synthesis, Characterization and Alpha Glucosidase Inhibition activity of new Phthalimide Derivatives - ALi, Hassan; H. Mohammed, Mohammed; H. Ismeal, Sajida (Iraqi Journal of Pharmaceutical Sciences, 2018)
Three of imide intermediate products were synthesized by reacting of phthalic anhydride with glycine (2a), and tetrachloro phthalic anhydride with glycine , (S)-2-[(tert-Butoxycarbonyl)amino]-3-aminopropionic acid ( 2b,c) respectively in dry toluene with azeotropic removal of water using Dean- stark apparatus then carboxyl functional group activated by refluxing with thionyl chloride, the resulted acid chloride (3a-c) were reacted with different amine (5-flourouracil, 4-chloroaniline, 4-bromoaniline, 2-amino thiazole, and pyrrolidine) (4a-e) , the resulted products consider as the end products (5a-j) while the compounds (5k-o) required further reaction to deprotect aliphatic amine this achieved by treating the compounds with TFA to remove tert-Butoxycarbonyl group (6a-e). The alpha glucosidase inhibitory activity of some synthesized compounds (5a, 5f, 6a) were tested by using -glucosidase from Saccharomyces cerevisiae, p-nitrophenol glucopyranoside (pNPG) used as substrate and acarbose used as standard. All these test compounds shows excellent inhibitory activity according to IC50 values which is ranging from (4.61-7.32).